Relación entre el lapso detección del celo-inseminación y el porcentaje de preñez en vacas lecheras Celo-inseminación y porcentaje de preñez - Marini, P.R. (2010)
The aim of this work was to study the relationship between the duration of the period of time between heat detection and insemination and pregnancy rate in dairy cows and whether, if any, this relationship is affected by the season of the year or the bull. A retrospective observational study on 755 periods of time elapsed from estrus detection to artifi cial insemination of Holstein dairy cows was performed. Based on the duration of the aforementioned period cows were categorized into the three following groups: <6 hours, 6 to 12 hours and 12 to 18 hours. Independently of the low pregnancy rates observed during the four seasons all comparisons were statistically not signifi cant either among periods within season or between seasons within period or between bulls within period. It is concluded that the effectiveness of artifi cial insemination would not be affected by the time elapsed since heat detection and that this homogeneous behavior described for pregnancy rates is not affected by the season of the year or the source of the semen (bull) used.\n